A Neuroprotective Anesthetic Strategy: Ultrasound-Guided Dual Plexus Blockade for Clavicle Fixation Following Decompressive Craniectomy - Muhammad Husni Thamrin; Bara Adithya; Muhammad Dony Hermawan (HM Publisher, 2025)
Introduction: Anesthetic management for non-neurosurgical procedures in patients with recent severe traumatic brain injury (TBI) presents a formidable challenge. General anesthesia carries inherent risks of hemodynamic instability and increased intracranial pressure (ICP), which can precipitate devastating secondary brain injury. Regional anesthesia offers a neuroprotective alternative, though its application in this specific high-risk population is not extensively documented. Case presentation: A 24-year-old male, ASA status III-E, required open reduction and internal fixation of a clavicle fracture six days after an emergency decompressive craniectomy for an acute epidural hematoma. To mitigate neurological risk, a definitive anesthetic plan consisting of an ultrasound-guided dual plexus blockade was implemented. This involved a combination of an interscalene brachial plexus block (15 mL of 0.375% levobupivacaine) and a superficial cervical plexus block (10 mL of 0.375% levobupivacaine), supplemented with light, non-opioid sedation using dexmedetomidine. The 150-minute surgery was completed with exceptional hemodynamic stability, no requirement for airway manipulation, and no anesthetic or surgical complications. The patient remained comfortable and neurologically intact throughout. Conclusion: This case demonstrates that an ultrasound-guided dual plexus blockade is a safe, effective, and neurologically protective primary anesthetic technique for clavicle surgery in the post-craniotomy patient. By providing dense surgical anesthesia while preserving stable cerebral perfusion pressure, this approach represents a superior alternative to general anesthesia in this fragile patient population. We advocate for its consideration in similar clinical scenarios.